Development of Student Worksheets Based Inquiry using PhET Simulations to Enhance the Curiosity Attitude of High School Students - Roni Jarlis; Juli Supriyanti; Fildza Arief Syuhada; Ananto Ananto; Taufiqqurahman Taufiqqurahman; Santi Diana Putri; Putri Rahmi (Universitas Syiah Kuala, 2023)
The research aims to develop inquiry-based worksheets which are expected to increase students' curiosity about gas kinetic theory material. The inquiry approach method was developed with steps, giving problems, formulating problems, hypotheses, experiments, collecting data, analyzing data, and making conclusions. The method used is the ADDIE development method, which analyzes, designs, develops, implements, and evaluates. Developing inquiry-based worksheets and testing the effectiveness of these worksheets in the learning process. The research subjects were 22 class XI students of SMA N 4 Sijunjung. The instrument used was a student worksheet and a curiosity attitude questionnaire. Assessment of the student worksheet was carried out by validation tests of media experts, material experts, and questionnaires for teachers. The validation results of media experts showed 92.30% (very good), and media experts scored 90.21% (very good), while trials on teachers and students showed scores of 86.13% and 89.16% (very good). The results of the student worksheet effectiveness test used the medium criterion N-Gain test, value 0.32. This shows that inquiry-based worksheets equipped with Phet simulations deserve to be good teaching materials and can increase students' curiosity in high school physics learning on the kinetic theory of gases.